Workplace bullying among nurses in Bangladeshi government hospitals - Roy, Liton; Khan, AKM Dawlat (Asian Journal of Medical and Biological Research, 2020)
Bullying in the nurses’ workplace is a common, rising and worldwide problem. Workplace bullying is a persistent phenomenon that transmits harmful effects on health care organizations and the health system as a whole, including patients’ satisfaction. The workplace bullying impacts negatively on the performance of workers. A descriptive study was conducted among the 183 government register nurses in 8 government health care facilities at Chattogram in Bangladesh from July to August 2014. Most of the respondents were female (90.7%) and more than half of the respondents (52.5%) were between 30 and 39 years old. The study revealed that there are three type of bullying faced by the nurses. They are work related, person related and physically intimidating bullying. They faced several bullying related to their works. Of these, most of them (92.8%) faced ‘ignoring their opinions and views’. Respectively, in person related bullying, 93.4% were being ignored or facing a hostile reaction when they approach regarding their works; and in physically intimidating bullying, 95.0% were being shouted at or being the target of spontaneous anger or rage. In Bangladesh Nurses faced many challenges in healthcare system due to unavailable resources, more complex patients, increased nursing shortage, increased job insecurity, job stress, and increased recruitment costs for healthcare institutions. The study concluded that an in-depth study would be conducted to find out the root causes for the workplace bullying and also design a training program that addresses the root causes, involves all individuals from all levels, and provides skills for dealing with this phenomenon can promote a harmonious working environment. Asian J. Med. Biol. Res. March 2020, 6(1): 67-72